Healthcare-seeking behaviors and factors influencing non-adherence among cervical cancer patients attending Bugando Oncology Clinic in Mwanza, Tanzania: A qualitative Phenomenological study. - Bashari Nuru Kidaya; Joseph Rogathe Mwanga; Oscar Ottoman Muhini; Halima Mdemu Mwaisungu; Elisha Mabula Juma; Vivian Elikana Buremo (PLoS ONE)
Background In low- and middle-income countries, particularly in Tanzania, most patients with cervical cancer present with advanced-stage disease and exhibit non-adherence which results in increased numbers of patients with cancer-related deaths. The current study explores the health-seeking behavior of cervical cancer patients and the factors that influence their non-adherence to cancer care. Objective To explore the healthcare-seeking behaviors and identify factors influencing non-adherence among cervical cancer patients attending Bugando Medical Center's Oncology Clinic in Mwanza, Tanzania. Methods A qualitative phenomenological design was adopted to explore the lived experiences of 15 households with non-adherent cervical cancer patients, after obtaining patients' information from the chemo radiation treatment registries of Bugando Oncology Clinic in Mwanza, Tanzania. Data were generated through in-depth interviews with patients, and NVivo 12 qualitative computer software was used to aid analysis. Thematic content analysis was conducted to uncover underlying meanings and patterns in the data, providing valuable insights into the phenomena under investigation. Findings The study revealed poor adherence to treatment-seeking by most of the study informants in the form of delayed health-seeking at nearby health facilities. The limited capacity for correct cervical cancer diagnosis also pushed some of the informants to turn to self-medication including traditional remedies. The findings revealed delayed healthcare-seeking behavior and poor adherence to most of the study participants seeking medical care at nearby health facilities with limited capacity for correct cervical cancer diagnosis. Some turned to self-medications including traditional remedies. Financial constraints emerged as a major obstacle, affecting the affordability of treatments, transportation, and accommodation. Moreover, the malfunctioning radiotherapy machine posed a significant barrier to effective treatment. Limited comprehensive information on their condition, treatment options, and schedules further hindered adherence. Conclusion There is a need for improved access to an appropriate healthcare system and interventions to improve non-adherence to treatment of cervical cancer services, as well as increase public awareness, initiation of tools for good adherence of chemotherapy treatment and mass screening of cervical cancer risk factors and earlier diagnosis for better survival from the disease in Tanzania.